2024
DOI: 10.1186/s13195-024-01462-3
|View full text |Cite
|
Sign up to set email alerts
|

N, N-Dimethyltryptamine, a natural hallucinogen, ameliorates Alzheimer’s disease by restoring neuronal Sigma-1 receptor-mediated endoplasmic reticulum-mitochondria crosstalk

Dan Cheng,
Zhuo-Gui Lei,
Kin Chu
et al.

Abstract: Background Aberrant neuronal Sigma-1 receptor (Sig-1r)-mediated endoplasmic reticulum (ER)- mitochondria signaling plays a key role in the neuronal cytopathology of Alzheimer’s disease (AD). The natural psychedelic N, N-dimethyltryptamine (DMT) is a Sig-1r agonist that may have the anti-AD potential through protecting neuronal ER-mitochondrial interplay. Methods 3×TG-AD transgenic mice were administered with chronic DMT (2 mg/kg) for 3 weeks and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…In contrast, dysfunction of mitochondrial oxidative phosphorylation induces neurodegenerative disease processes. Studies have shown that a natural hallucinogen, N , N -dimethyltryptamine, contributes to the amelioration of AD by modulating oxidative phosphorylation in an in vitro model of AD ( Cheng et al, 2024 ), so similarly p -HBA may play a role in ameliorating the AD C. elegans model by mediating the oxidative phosphorylation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, dysfunction of mitochondrial oxidative phosphorylation induces neurodegenerative disease processes. Studies have shown that a natural hallucinogen, N , N -dimethyltryptamine, contributes to the amelioration of AD by modulating oxidative phosphorylation in an in vitro model of AD ( Cheng et al, 2024 ), so similarly p -HBA may play a role in ameliorating the AD C. elegans model by mediating the oxidative phosphorylation pathway.…”
Section: Discussionmentioning
confidence: 99%